Collaborative Governance as Mitigation of Money Politics in Elections Based on Local Resilience - Muhamad Basri; Suharto, Didik Gunawan; Drajat Tri Kartono (Jurnal Ilmiah Administrasi Publik, 2026)
This article examines the role of collaborative governance as a means of mitigating money politics through the lens of local resilience, using the Systematic Literature Review (SLR) method with the PRISMA approach. The study aims to identify the key factors in multi-actor collaboration that strengthen local resilience and curb the practice of money politics. Data were collected from selected scholarly articles and analyzed systematically to identify patterns, challenges, and opportunities. The findings indicate that effective collaboration enhances local resilience and reduces the space for money politics through transparency, participation, and governance innovation. The implications of this research highlight the importance of strengthening local capacity and promoting collaboration-based policy reforms. This study contributes to the development of a collaborative governance model designed to prevent money politics at the local level.